Solid Phase Transformation and Stability of Carbamazepine-adipic Acid Co-Crystal - Mohd Rohaizam, Mohd Sidek (2012)
Co-crystal is a mixed crystal or crystal that contains two or more different molecules. In this study, the solid phase transformation of CBZ-AA co-crystal and solubility of carbamazepine (CBZ) and adipic acid (AA) is examined. In this dissertation, the solubility of CBZ and AA via HPLC and gravimetric methods are reported. On the other hand, the study of solid phase transformation is planned to proceed via slurry co-crystallization method. The result shows the solubility of CBZ and AA via gravimetric and HPLC method is increased as the temperature increased from 25 ˚C to 50 ˚C. TGA analysis shows the weight changed of CBZ is 96.21 % at decomposed temperature of 250 ˚C and 94.47 % for AA at 220 ˚C decomposed temperature. The wavenumbers corresponding to CBZ and AA is obtained from FTIR analysis. Due to time limitation, the phase transformation of CBZ-AA co-crystal is suggested to be continued by another student in the future.